Corporate genome screening India (CoGsI) identified genetic variants association with T2D in young Indian professionals - Shah Fahad Husami; Tavleen Kaur; Love Gupta; Garima Rastogi; Lakhvinder Singh; Pooja Meena; Indu Sharma; Hemender Singh; Varun Sharma (Scientific Reports)
Abstract Rising cases of type 2 diabetes (T2D) in India, especially in metropolitan cities is an increasing concern. The individuals that were most affected are young professionals working in the corporate sector. However, the corporate sector has remained the least explored for T2D risk predisposition. Considering corporate employees’ lifestyles and the role of gene-environment interaction in T2D susceptibility, the study aims to find genetic variants associated with T2D predisposition. In this first kind of study, 680 young professionals (284 T2D cases, and 396 controls) were diagnosed and screened for 2658 variants on an array designed explicitly for the CoGsI study. The variant filtering was done at Bonferroni p-value of 0.000028. The genetic data was analysed using PLINK v1.09, SPSS, R programming, VEP tool, and FUMA GWAS tool. Interestingly, 42 variants were associated with the T2D risk. Out of 42, three missense variants (rs1402467, rs6050, and rs713598) in Sulfotransferase family 1 C member 4 (SULT1C4), Fibrinogen Alpha Chain (FGA), and Taste 2 Receptor Member 38 (TAS2R38) and two untranslated region (UTR) variants (rs1063320 and rs6296) in Major Histocompatibility Complex, Class I, G (HLA-G) and 5-Hydroxytryptamine Receptor 1B (HTR1B) were associated with the T2D risk. CoGsI identified potential genomic markers increasing susceptibility to the early onset of T2D. Present findings provide insights into mechanisms underlying T2D manifestation in corporate professionals due to genetics interacting with occupational stress and urban lifestyles.